Pengaruh Laverage, Firm Size, Dan Return On Asset Terhadap Tax Avoidance Pada Perusahaan Manufaktur Sub Sektor Plastik danKemasan Yang Terdaftar DiBursa Efek Indonesia Tahun 2017 - 2021 - Gultom, Matius Jonathan; Liswanty, Ina (JSAP : Journal Syariah and Accounting Public, 2023)
The aim of this research is to analyze the factors influencing tax avoidance. The variables tested in this research are leverage, firm size, and return on assets as independent variables, with tax avoidance as the dependent variable. The population used in this research consists of 8 companies selected based on the purposive sampling method. The data analysis technique carried out in this research is multiple linear regression analysis using the SPSS version 26 application. The results of this research indicate that, in terms of leverage, the partial leverage does not have a significant effect on tax avoidance, and firm size does not have a significant effect on tax avoidance. However, return on assets has a significant effect on tax avoidance. The simultaneous test results show that leverage, firm size, and return on assets have an effect on tax avoidance..